Etična literarna veda med kakofonijo in pluralnostjo - Virk, Tomo (Primerjalna književnost, 2017)
Although the so-called ethical turn in literary studies happened in the eighties and nineties of the twentieth century, the topic "Literature and Ethics" in its various forms and denominations has been present since the beginnings of the reflection on literature. This treatise summarizes the most prominent research directions of this topic and attempts to point out their strengths and weaknesses. As the most burning deficiency, it identifies the so-called cacophony of ethical approaches to literature, characterized by the lack of theoretical and methodological self-reflection. In order to overcome this deficiency, it proposes to scrutinize some basic concepts and relations of the ethical literary criticism, such as the range of terms "ethics" and "literature", the relation between ethics and morality and between ethics and politics, the problem of aesthetic autonomy in relation to the ethical evaluation, the problematic issue of aesthetic re-evaluation on the ground of ethical evaluation, etc. In the conclusion, the treatise stresses the general importance of ethical research in literary studies and points out (the ethical) obligations of researchers engaging in ethical literary criticism.
Keywords: literatura in etika; literature and ethics; literarna veda; literary criticism; literary science; etični obrat; ethical turn; ethics and morality; etika in morala; literature and politics; literatura in politika; aesthetic autonomy; estetska avtonomija